My first ukrainian tools in the shed picture book with english translations ebook Teach & learn basic ukrainian words for children, #5. - S, Aneta (Teach & Learn Basic Ukrainian words for Children, 2023)
Want to Teach Your Kids the Names of Tools in Ukrainian? Wonder How They're Pronounced? Enhance your learning experience with our complimentary audio recordings. Follow the link in the book to not only read but also listen and familiarize yourself with authentic Ukrainian pronunciation. Delight in learning Ukrainian with our vivid picture book! Key Features of the Book: Ukrainian Names for Tools. Vibrant Illustrations of Each Tool. English Translations. English Transliteration - A guide to the Ukrainian pronunciation of each name. Complimentary Ukrainian Audio - Access via the link in the book for an immersive learning experience. What Sets Our Book Apart? Each Tool Featured on a Dedicated Page. Stunning Full-Color Artwork on All Pages. Complimentary Ukrainian Audio.